Pengaruh Penambahan Ekstrak Serai (Cymbopogon Citratus) dan Gula Terhadap Sifat Fisik, Kimia, dan Tingkat Kesukaan Kunyit Instan - Wahyu Pratama; Dwiyati Pujimulyani; Ichlasia Ainul Fitri (Journal of Food and Agricultural Technology, 2025)
Turmeric is a tropical plant from Asia and has now spread to subtropical regions around the world. Instant turmeric is generally in the form of a small powder and is easily dissolved in water. The manufacture of instant turmeric using turmeric and sugar raw materials and lemongrass is an effort to utilize local foodstuffs. The use of lemongrass as an additional ingredient is expected to increase the preference for instant powder. Purpose To determine the effect of variations in the addition of tablegrasshopper extract and sugar on the physical, chemical, and preference levels of instant turmeric. completely randomized design 2 factors, namely the addition of the amount of sugar (500; 1000; and 1500 g) and the variation of adding lemongrass extract (0; 20; and 40 ml). The instant turmeric products produced were then physically tested and the level of preference, and the selected instant turmeric was chemically analyzed (moisture content, antioxidant activity of DPPH (2,2-diphenyl-1-pycrylhydryl) and total phenol). The data obtained was statistically calculated with ANOVA and a 95% confidence level. The results showed that the addition of the amount of sugar (500; 1000; and 1500 g) and the variation of the addition of lemongrass extract had an effect on the resulting turmeric. The selected instant turmeric product is the addition of 20 g of lemongrass extract and the addition of 1000 g of sugar which has a moisture content of 0.94%, DPPH antioxidant activity of 54.63% RSA, and a total phenol of 4.41 mg EAG/g bk.)